Structural social relations and cognitive ageing trajectories: evidence from the Whitehall II cohort study. (7th November 2017) - Elovainio, Marko; Sommerlad, Andrew; Hakulinen, Christian; Pulkki-Råback, Laura; Virtanen, Marianna; Kivimäki, Mika; Singh-Manoux, Archana
Abstract: Background: Social relations are important for health, particularly at older ages. We examined the salience of frequency of social contacts and marital status for cognitive ageing trajectories over 21 years, from midlife to early old age. Methods: Data are from the Whitehall II cohort study, including 4290 men and 1776 women aged 35–55 years at baseline (1985–88). Frequency of social contacts and marital status were measured in 1985–88 and 1989–90. Assessment of cognitive function on five occasions (1991–94, 1997–99, 2003–04, 2007–09 and 2012–13) included the following tests: short-term memory, inductive reasoning, verbal fluency (phonemic and semantic) and a combined global score. Cognitive trajectories over the study period were analysed using longitudinal latent growth class analyses, and the associations of these latent classes (trajectory memberships) with social relations were analysed using multinominal logistic regression. Results: More frequent social contacts [relative risk (RRR) 0.96, 95% confidence interval (CI) 0.94 – 0.98] and being married (RRR 0.70, 95% CI 0.58 – 0.84) were associated with lower probability of being on a low rather than high cognitive performance trajectory over the subsequent 21 years. These associations persisted after adjustment for covariates. Of the sub-tests, social relations variables had the strongest association with phonemic fluency (RRR 0.95, 95% CI 0.94 – 0.97 for frequent contact; RRR 0.59, 95% CI 0.48 – 0.71 for being married). Conclusions: More frequent social contacts and having a spouse were associated with more favourable cognitive ageing trajectories. Further studies are needed to examine whether interventions designed to improve social connections affect cognitive ageing.